2020
DOI: 10.1177/0194599820978276
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Tracheostomy Decannulation in Adult Laryngotracheal Stenosis

Abstract: Objective Predictors of tracheostomy decannulation in patients with laryngotracheal stenosis are not fully known, making prognosis difficult. The aim was to identify predictors of tracheostomy decannulation in adult patients with acquired stenosis of the larynx and/or trachea who were tracheostomy dependent. Study Design Case series. Setting Academic teaching hospital. Methods A total of 103 consecutive adult patients with laryngotracheal stenosis who were tracheostomy dependent and seen by the otolaryngology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“… 17 Another study by Snow et al reported that for those with subglottic or tracheal narrowing, airway firm scarring as opposed to granulation had a greater association with tracheostomy dependence. 8 Applying this notion to PGS, significant scarring would be more likely to result in a higher Bogdasarian classification and increased likelihood of complete immobility. As Snow et al described for SGS and tracheal stenosis, we similarly identified a significant relationship on multivariate analysis between complete BVFI and decreased likelihood of decannulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 17 Another study by Snow et al reported that for those with subglottic or tracheal narrowing, airway firm scarring as opposed to granulation had a greater association with tracheostomy dependence. 8 Applying this notion to PGS, significant scarring would be more likely to result in a higher Bogdasarian classification and increased likelihood of complete immobility. As Snow et al described for SGS and tracheal stenosis, we similarly identified a significant relationship on multivariate analysis between complete BVFI and decreased likelihood of decannulation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have identified certain factors in patients with laryngotracheal stenosis that are associated with prolonged tracheostomy placement. 7 8 9 To date, only one study has evaluated risk factors solely in patients with a diagnosis of postintubation PGS. 5 The pathophysiology of this condition is unique, and factors associated with both the development and consequences of PGS after intubation may differ from other etiologies.…”
Section: Introductionmentioning
confidence: 99%
“…Laryngotracheal stenosis, which involves progressive airway fibrosis and narrowing, confers significant morbidity 16,105 . The resulting obstruction often necessitates intervention, 106‐110 with variable long‐term outcomes 111,112 . Intravenous corticosteroids have known efficacy in the treatment of acute airway edema and in prevention of postextubation laryngeal edema 11,113,114 .…”
Section: Laryngotracheal Stenosis and Other Laryngeal Disordersmentioning
confidence: 99%
“…16,105 The resulting obstruction often necessitates intervention, [106][107][108][109][110] with variable long-term outcomes. 111,112 Intravenous corticosteroids have known efficacy in the treatment of acute airway edema and in prevention of postextubation laryngeal edema. 11,113,114 However, prolonged use of SCSs for laryngotracheal stenosis is seldom indicated.…”
Section: Laryngotracheal Stenosis and Other Laryngeal Disorders Laryn...mentioning
confidence: 99%
“…10 Consequently, it is important to recognize and understand the differences in patients that may successfully undergo tracheostomy decannulation. 9 Prior literature has illustrated that patients diagnosed and treated for type I PGS show promise for excellent prognosis post-operatively with decannulation rates near 80%. 11 Also, a recent case series reported patients most likely to be decannulated after receiving a tracheostomy for laryngotracheal stenosis underwent early otolaryngologic evaluation and had minimal firm scar formation in their granulation tissue.…”
Section: Introductionmentioning
confidence: 99%